2018
DOI: 10.1021/acsaem.8b01113
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light-Driven Dye-Sensitized Photocatalytic Hydrogen Production by Porphyrin and its Cyclic Dimer and Trimer: Effect of Multi-Pyridyl-Anchoring Groups on Photocatalytic Activity and Stability

Abstract: The monomer, dimer, and trimer of 5,15-diphenyl-10,20di(pyridin-4-yl)porphyrin are used to investigate the multi-anchoring eff ect on TiO2 for visible light-driven photocatalytic hydrogen production in a water medium. Further, the porphyrin trimer is prepared and analyzed by nuclear magnetic resonance (NMR) spectroscopy, absorption spectroscopy, electrochemical voltammetry, fast atom bombardment (FAB) mass spectroscopy, and density functional theory (DFT) computation. The results of this study indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 85 publications
(149 reference statements)
3
15
0
Order By: Relevance
“…However, no obvious change in the absorption band of Dimer‐2 was observed. The results above indicated that Dimer‐2 had the best binding mode with TiO 2 , therefore benefiting its photocatalytic performance under long‐term irradiation [83] …”
Section: Photosensitizers Constructed With Macrocyclic Compoundsmentioning
confidence: 81%
See 2 more Smart Citations
“…However, no obvious change in the absorption band of Dimer‐2 was observed. The results above indicated that Dimer‐2 had the best binding mode with TiO 2 , therefore benefiting its photocatalytic performance under long‐term irradiation [83] …”
Section: Photosensitizers Constructed With Macrocyclic Compoundsmentioning
confidence: 81%
“…The results above indicated that Dimer-2 had the best binding mode with TiO 2 , therefore benefiting its photocatalytic performance under long-term irradiation. [83] Yuan Sun et al creatively combined commercial porphyrin derivative dye Chl and indoline-rhodanine dye Ind together by ester bond to form the new dual-moieties dyad dye (donated as Dyad) ( Figure 41 and Table 1, No. 117-119).…”
Section: Photosensitizers Constructed With Macrocyclic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, various strategies have been explored to improve the WS efficiency under solar illumination. The band gap can be narrowed and light absorption extended to longer wavelengths by doping with non-metal atoms [21,22], with organic dyes [23] such as ruthenium complexes [24], porphyrins [25], or graphene oxide [26][27][28][29]. Another strategy to improve the PC efficiency relies on the use of hybrid metal nanoparticles/semiconductor nanostructures [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44], in order to reduce the electron-hole recombination and/or to harvest the visible light owing to plasmonic enhanced optical absorption [29,30,45].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the anchoring mode of porphyrin derivatives was evaluated by means of surface silanization by APTES (3-aminopropyl triethoxysilane), allowing an amide covalent grafting on TiO 2 and SiO 2 nanoparticles [34], or surface modification by maleic anhydride of a Fe 3 O 4 @SiO 2 @TiO 2 magnetic composite, achieving in both cases stable anchoring and photocatalytic activity [35]. Moreover, using a dimer or trimer of porphyrin with a pyridyl anchoring group, which formed H-bonds on the TiO 2 surface, enhanced both hydrogen generation rate under visible light and stability [36]. A few applications of specifically synthesized metal-free phthalocyanines have also been reported.…”
Section: Organic Dye-sensitized Tiomentioning
confidence: 99%